PERAN GURU DALAM MENUMBUHKAN MOTIVASI BELAJAR SISWA PADA PEMBELAJARAN FIQIH KELAS 3 DI MIN 3 SAMBAS - Dewi Saputri; Usna; Ulan Dari (CV. Adiba Aisha Amira, 2026)
Teachers play a very important role in determining the success of the learning process. One of the main roles of teachers is to foster student motivation to learn in order to create an active and meaningful learning atmosphere. This study aims to describe the role of teachers in fostering student motivation to learn in Fiqh lessons in Grade III at MIN 3 Sambas and to identify the factors that support and hinder this. This study uses a descriptive qualitative approach with the research subjects being Fiqh teachers and third-grade students at MIN 3 Sambas. Data were collected through observation, interviews, and documentation, then analysed descriptively through data reduction, data presentation, and conclusion drawing. The results showed that teachers played an important role in fostering student motivation through various strategies, including using varied learning methods, setting a good example, creating a pleasant learning atmosphere, and rewarding students' efforts. Supporting factors included the availability of learning media, school environment support, and good teacher-student relationships. Hindering factors included differences in student characteristics and limited learning time. Thus, it can be concluded that the role of teachers is very influential in fostering student motivation in learning Fiqh. Teachers who are able to innovate and adapt teaching methods to the needs of students can increase their interest and enthusiasm for learning Fiqh